Review of Asherman syndrome and its hysteroscopic treatment outcomes: experience in a low-resource setting - Melkamu Siferih; Thomas Gebre; Fufa Hunduma; Abraham Abebe; Akebom Gebremichael; Habtamu Sewunet; Tewodros Shibabaw (BMC, 2024)
Abstract Background Asherman syndrome is one of the endometrial factors that influence a woman's reproductive capacity. However, in our context, it needs to be well-documented. This study aimed to evaluate the clinical characteristics and hysteroscopic treatment outcomes of Asherman syndrome. Method A retrospective follow-up study from January 1, 2019, to December 31, 2022, was conducted on cases of Asherman syndrome after hysteroscopic adhesiolysis at St.Paul's Hospital in Addis Ababa, Ethiopia. Clinical data were collected via telephone survey and checklist. Epidata-4.2 and SPSS-26 were employed for data entry and analysis, respectively. Result A total of 177 study participants were included in the final analysis. The mean patient age was 31 years (range: 21-39) at the initial presentation, and 32.3 years (range: 22-40) during the phone interview. The majority of the patients (97.7%) had infertility, followed by menstrual abnormalities (73.5%). Among them, nearly half (47.5%) had severe, 38.4% had moderate, and 14.1% had mild Asherman syndrome. The review identified no factor for 51.4% of the participants. Endometrial tuberculosis affected 42 patients (23.7%). It was also the most frequent factor in both moderate and severe cases of Asherman syndrome. Only 14.7% of patients reported menstrual correction. Overall, 11% of women conceived. Nine patients miscarried, three delivered viable babies, and six were still pregnant. The overall rate of adhesion reformation was 36.2%. Four individuals had complications (3 uterine perforations and one fluid overload) making a complication rate of 2.3%. Conclusion Our study revealed that severe forms of Asherman syndrome, which are marked by amenorrhea and infertility, were more common, leading to incredibly low rates of conception and the resumption of regular menstruation, as well as high recurrence rates. A high index of suspicion for Asherman syndrome, quick and sensitive diagnostic testing, and the development of a special algorithm to identify endometrial tuberculosis are therefore essential. Future multi-centered studies should focus on adhesion preventive techniques.